Two independent mutations are required for temperature-sensitive cell transformation by a Rous sarcoma virus temperature-sensitive mutant. - Nishizawa, M (1985)
We molecularly cloned the src coding region of tsNY68, a mutant of Rous sarcoma virus temperature sensitive (ts) for transformation, and constructed a series of ts wild-type recombinant src genes. DNA containing the hybrid genes was transfected into chicken cells together with viral vector DNA and helper viral DNA, and infectious transforming viruses were recovered. Characterization of these recombinant viruses indicated that at least two mutations are present in the 3' half of the mutant src gene, both of which are required for ts. Nucleotide sequence analysis revealed three differences in the deduced amino acid sequence compared with the parental virus. Two of these changes, a deletion of amino acids 352 to 354 and an amino acid substitution at position 461, are responsible for the ts phenotype.